Assessment of smallholder farmers' awareness of bean fly (Ophiomyia spp.) and management practices in central and northern Malawi: Implications for resistance breeding. (January 2021) - Nkhata, Wilson; Shimelis, Hussein; Melis, Rob; Chirwa, Rowland; Mathew, Isack; Shayanowako, Admire; Mzengeza, Tenyson
Abstract: The production of common bean ( Phaseolus vulgaris L.) in East and Southern Africa (ESA) regions falls short of the demand partly due to insect pests and diseases, and a lack of high yielding varieties. Bean fly ( Ophiomyia spp.) is one of the most devastating field insect pests of common bean in ESA and the development of host plant resistance to bean fly is an important strategy to combat yield losses caused by this insect pest. A survey involving 195 farmers in Kalira, Chipuka, Champhira and Luwerezi Agricultural Extension Planning Area (EPAs) in Malawi was conducted to assess their awareness of bean fly and their varietal selection criteria. Only 45% of the respondent farmers were aware of the bean fly pest and practiced integrated insect pest management strategies that included the use of chemical and botanical insecticides, and cultural control methods. The level of education, previous bean fly experience and farmer's location significantly (P < 0.001) influenced their awareness of bean fly. Principal component analysis identified disease resistance (with a loading score of (0.87), grain yield (0.34), insect pest resistance (0.35), early maturity (0.48) and cooking time (0.14) as the most important traits that influence farmers' varietal choice. Implementation of strategies such as farmer field schools and on farm field trials relating to bean fly and also introduction of adult literacy learning centers will promote awareness of bean fly. Therefore, common bean breeding programs should integrate and prioritize selection for these traits in varietal design for successful adoption of new cultivars among farmers in these and similar ecologies.